Analisis Persepsi Masyarakat terhadap Pendidikan TPQ Permata Desa Tapen Kecamatan Wanadadi Kabupaten Banjarnegara - Nurul Farida; Robingun Suyud El Syam; Rifqi Aulia Rahman (IHSANIKA : Jurnal Pendidikan Agama Islam, 2023)
This research aims to explore public perceptions of education at the Permata Al-Qur'an Education Park (TPQ), Tapen Village. With a qualitative approach, this research involves direct observation, interviews, and documentation to understand social phenomena from the participant's perspective. Tapen Village was chosen as the research location because of its relevance to the topic of community participation in developing children's education in non-formal education institutions.The results of the analysis show that the people of Tapen Village have a very positive perception of education at TPQ Permata, especially in academic, economic and social aspects. Active support from various levels of society, participation in economic and social activities, and community solidarity are key points in the success of TPQ Permata. However, several inhibiting factors, such as busy parents and lack of awareness of the importance of early education, need to be taken into consideration in efforts to improve the quality of education at TPQ Permata.This research provides in-depth insight into the dynamics of community participation in supporting non-formal education institutions, especially TPQ. The implications of these findings can be used as a basis for developing further strategies to strengthen the role of TPQ Permata in shaping the spiritual character and morals of the younger generation.